The examination of the relationship between learning motivation and learning effectiveness: a mediation model of learning engagement - Hong Lei; Chiwei Chen; Limei Luo (Humanities & Social Sciences Communications, 2024)
Abstract In the past decade, China has entered the process of universalization of higher education, however, with the popularization of higher education, the issue of education quality has become more important than ever. Therefore, the main objective of this study was to explore the relationship between learning motivation and learning effectiveness, the mediation effect of learning engagement on learning motivation and learning effectiveness, and the moderation effect of students’ personality traits on the relationship between learning motivation and learning effectiveness. It was found that (1) Learning motivation had a significant positive impact on learning effectiveness; (2) Learning motivation had a significant positive effect on learning engagement; (3) Learning engagement had a significant positive impact on learning effectiveness; (4) Learning engagement had a partial mediation effect on learning motivation and learning effectiveness. (5) Personality traits had a moderation effect on the relationship between learning motivation and learning effectiveness. It was suggested that college students should stimulate their motivation for independent learning, enhance their motivation for learning, and cultivate the ability to learn independently in learning. At the same time, in the classroom, teachers should innovate teaching methods, mobilize students’ interest in learning, and cultivate students’ initiative. In addition, schools should actively carry out themed lectures to cultivate students’ correct learning attitudes. In terms of the influence of personality traits on the relationship between learning motivation and learning effectiveness should not be ignored, and appropriate attention should be paid to improving learning effectiveness. Different personality traits should be further explored.